Methamphetamines and Acetabular Reoperation Rates: Poor Outcomes From the Front Lines. Issue 12 (December 2021) - Zusman, Natalie L.; Woelber, Erik; McKibben, Natasha S.; Gallacher, David M.; Thompson, Austin R.; Friess, Darin M.; Working, Zachary M.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: To compare acetabular fracture reoperation rates within 1 year of surgery in methamphetamine ("meth") abusers and abstainers. Design: Retrospective database analysis. Setting: Level 1 academic trauma facility, 2008–2018. Patients/Participants: Three hundred seventy-one patients who underwent unilateral traumatic acetabular open reduction internal fixation during the study period, 36 of whom abused methamphetamines through self-report or toxicology. One hundred four were excluded for indeterminate abuse histories. Intervention: Open reduction internal fixation. Main Outcome Measurements: Reoperation resulting from major surgical complications, including hematoma, seroma, deep wound infection, failure of fixation, or arthrosis with conversion to arthroplasty. Results: More than 10% of our cohort used meth, representing patients who were a mean 8 years younger and sustained a higher rate of high-energy mechanisms than sober peers. Meth abusers had a greater than 2-fold reoperation rate at 90 days and 1 year compared with abstainers (17% vs. 7% and 25% vs. 11%, respectively). The adjusted odds ratio of 1-year reoperation in meth users was 3.2 (confidence interval 1.2–8.5, P = 0.03). The adjusted 1-year survival of native hip after acetabular fractures in meth users approaches 55%. Conclusions: Methamphetamine use is a nonmodifiable factor associated with a 3-fold increase in adjusted odds for 1-year reoperation after surgical fixation of acetabular fractures. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.